Os fenômenos "Déficit de socialização" e "Falta de sentido" e suas consequências na práxis docente - Cochete, Jéssica Lima [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The present Undergraduate Thesis analyses situations lived by students of the sixth and seventh years of the Elementary School. These situations were related to me, and I observed. The subject of analysis are students that I lived together in the school context, knew their histories, and developed affectivity compatible with my work as a teacher. The socialization problems were categorized as the phenomena “Deficit of Socialization” and “Lack of Meaning”, described by Juan Carlos Tedesco (1998). In other words, to observe how present-day children and teenagers manifest that. Also, to study how these students behave in school routine and what are the consequences in education. Among the consequences, is possible to highlight the low self-esteem and the bullying. As the objective of this assignment is an in-depth analysis of the behavior of these students, the object of study will be the students of the sixth and seventh year for whom the author of this monography teaches. Through a comparative study between the book and the reality, this monograph deals mainly with the function of the teacher as a reference in the lives of his/her students, not only in the aspect of teach-learning, but also in a society where some family members believe that the function of to teach moral and ethical values to their children is only of the teacher and is not fulfilling their own role. Finally, this Undergraduate Thesis has as objective to demonstrate the benefits of a more affectionate attitude toward leaners.

O objetivo do presente Trabalho de Conclusão de Curso foi o de analisar situações a mim relatadas e por mim observadas de alunos pertencentes ao sexto e sétimo ano do Ensino Fundamental. São alunos com quem convivi durante um período semestral letivo, de quem conheci alguns detalhes sobre suas histórias pessoais e por quem desenvolvi afetividades compatíveis com o meu papel de professora. Os problemas de socialização observados foram categorizados como os fenômenos “Déficit de Socialização” e “Falta de Sentido”, descritos por Juan Carlos Tedesco (1998). Em outras palavras, observar como esses fenômenos aparecem em crianças e adolescentes da atualidade na rotina escolar e quais são as suas consequências na educação formal desses atores em geral. Entre as consequências, o trabalho destaca a baixa autoestima e o bullying. Por meio de um estudo comparado entre a obra de Tedesco e a realidade, esta monografia trata, sobretudo, da função do docente como referência na vida de seus educandos, não só no aspecto do ensino e da aprendizagem, mas, também, de uma sociedade em que alguns familiares acreditam que o ensino de valores morais e éticos para seus filhos faz parte do trabalho do professor. Finalmente, este TCC busca mostrar os benefícios de uma atitude mais afetiva para com os educandos.
The "Socialization deficit" and "Lack of meaning" phenomena and their consequences in teaching practice
Keywords: Deficit of socialization; Lack of meaning; Bullying; Affectivity; Teacher-student relationship; Déficit de socialização; Falta de sentido; Afetividade; Relação professor-aluno